Tumor protein 53 mutations are enriched in diffuse large B-cell lymphoma with irregular CD19 marker expression - Marina Kazantseva; Noelyn A. Hung; Sunali Mehta; Imogen Roth; Ramona Eiholzer; Alison M. Rich; Benedict Seo; Margaret A. Baird; Antony W. Braithwaite; Tania L. Slatter (Scientific Reports, 2017)
Abstract Accumulating evidence suggests tumor protein 53 (p53) promotes correct cellular differentiation. Thus, mutant TP53 may be more frequent in tumors with irregular differentiation. This study investigated whether TP53 mutations were more frequent in diffuse large B cell lymphoma (DLBCL) that lacked the B cell lineage marker CD19. Sixteen CD19 negative and 78 CD19 positive DLBCL were sequenced for TP53 mutations. Twenty nine tumors had TP53 mutations and were associated with poorer survival. Mutant TP53 was more frequent in CD19 negative lymphomas (81% versus 21%, p < 0.0001). Analysis of other B cell markers revealed a lack of paired box 5 (PAX5) in CD19 positive lymphomas with mutant TP53 (50%), which was more frequent compared to tumors with wild-type TP53 (15%, p = 0.002). In summary, DLBCL lacking CD19 or PAX5 expression were more likely to have mutant TP53, suggesting irregular B cell marker phenotypes are associated with TP53 mutation.